New structural insights into Golgi Reassembly and Stacking Protein (GRASP) in solution - Mendes, Luis F. S.; Garcia, Assuero F.; Kumagai, Patricia S.; Morais, Fabio R. de [UNESP]; Melo, Fernando A. [UNESP]; Kmetzsch, Livia; Vainstein, Marilene H.; Rodrigues, Marcio L.; Costa-Filho, Antonio J. (Nature Publishing Group, 2016)
Among all proteins localized in the Golgi apparatus, a two-PDZ (PSD95/DlgA/Zo-1) domain protein plays an important role in the assembly of the cisternae. This Golgi Reassembly and Stacking Protein (GRASP) has puzzled researchers due to its large array of functions and relevance in Golgi functionality. We report here a biochemical and biophysical study of the GRASP55/65 homologue in Cryptococcus neoformans (CnGRASP). Bioinformatic analysis, static fluorescence and circular dichroism spectroscopies, calorimetry, small angle X-ray scattering, solution nuclear magnetic resonance, size exclusion chromatography and proteolysis assays were used to unravel structural features of the full-length CnGRASP. We detected the coexistence of regular secondary structures and large amounts of disordered regions. The overall structure is less compact than a regular globular protein and the high structural flexibility makes its hydrophobic core more accessible to solvent. Our results indicate an unusual behavior of CnGRASP in solution, closely resembling a class of intrinsically disordered proteins called molten globule proteins. To the best of our knowledge, this is the first structural characterization of a full-length GRASP and observation of a molten globule-like behavior in the GRASP family. The possible implications of this and how it could explain the multiple facets of this intriguing class of proteins are discussed.